Bioactive compounds in different acerola fruit cultivares - Mariano-Nasser, Flávia Aparecida De Carvalho [UNESP]; Nasser, Maurício Dominguez [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Ramos, Juliana Arruda [UNESP]; Vieites, Rogério Lopes [UNESP]; Pagliarini, Maximiliano Kawahata (Universidade Estadual de Londrina, 2017)
The increased consumption of acerola in Brazil was triggered because it is considered as a functional food mainly for its high ascorbic acid content, but the fruit also has high nutritional value, high levels of phenolic compounds, total antioxidant activity, anthocyanins and carotenoids in its composition. The objective was to evaluate the chemical, physical-chemical and antioxidant activity of eight varieties of acerola tree. The acerolas used in the research were the harvest 2015, 8 varieties: BRS 235 - Apodi, Mirandópolis, Waldy - CATI 30, BRS 238 - Frutacor, Okinawa, BRS 236 - Cereja, Olivier and BRS 237 - Roxinha, from the Active Bank Germplasm APTA Regional Alta Paulista in Adamantina - SP. Avaluated the following attributes: pH, titratable acidity, soluble solids, reducing sugar, instrumental color, ascorbic acid, total phenolics, flavonoids and antioxidant activity. The design was completely randomized, 8 varieties and 3 replications of 20 fruits each. Acerola fruit of the analyzed varieties prove to be good sources of phenolic compounds and antioxidant activity, ensuring its excellent nutritional quality relative to combat free radicals. The variety BRS 236 - Cereja presents higher ascorbic acid content, antioxidant activity and phenolic compounds, and the lowest value for flavonoid, which was higher than the other cultivars, especially Olivier and Waldy CATI-30.
Keywords: Antioxidants; Malpighia emarginata Sessé & Mociño ex DC; Polyphenols; Secondary metabolism